The Return of the Cultural Exception and its Impact on International Agreements (Global Media Journal - German Edition, 2014)
This essay examines the influence of the French concept of the “cultural exception” on European media policy and international agreements. After briefly reviewing the historical background of the cultural exception in France, the essay describes how demands for the cultural exception and those for diversity affect inter-/transnational agreements within the European Union and around the world. Special focus is placed on the current secret EU/US Transatlantic Trade and Investment Partnership Agreement (TTIP) negotiations that nearly failed because of France’s insistence that media and culture be exempted. The author argues that the concept of the “cultural exception” has been revived in recent years. However, due to the dual character of media (which is both a cultural and economic good), and the lack of a global media policy, the culture and trade debate will continue.
Keywords: cultural exception; cultural diversity; Transatlantic Trade and Investment Partnership Agreement (TTIP); Trans-Atlantic Free Trade Agreement (TAFTA); European Union; USA